Toward a multidimensional model of athletes' commitment to coach-athlete relationships and interdependent sport teams: A substantive-Methodological synergy - Jackson, B.; Gucciardi, Daniel; Dimmock, J. (Human Kinetics, 2014)
Drawing from a three-factor model of organizational commitment, we sought to provide validity evidence for a multidimensional conceptualization designed to capture adolescent athletes’ commitment to their coach–athlete relationship or their team. In Study 1, 335 individual-sport athletes (Mage = 17.32, SD = 1.38) completed instruments assessing affective, normative, and continuance commitment to their relationship with their coach, and in Study 2, contextually modified instruments were administered to assess interdependent sport athletes’ (N = 286, Mage = 16.31, SD = 1.33) commitment to their team. Bayesian structural equation modeling revealed support for a three-factor (in comparison with a single-factor) model, along with relations between commitment dimensions and relevant correlates (e.g., satisfaction, return intentions, cohesion) that were largely consistent with theory. Guided by recent advancements in Bayesian modeling, these studies provide a new commitment instrument with the potential for use and refinement in team- and relationship-based settings and offer preliminary support for a conceptual framework that may help advance our understanding of the factors underpinning individuals’ engagement in sport.